Biases in simulating Amazon moisture transport: a convection-permitting versus regional climate model intercomparison - Murilo Ruv Lemes; Gilberto Fisch; Lincoln M. Alves; José Augusto Veiga; Gilvan Sampaio; Richard Bassett; Douglas Lowe; Adriane L. Brito; Polyanna da Conceição Bispo (Climate Dynamics, 2026)
The dynamics of moisture transport in the Amazon are key to the South American water cycle. Convection-permitting regional climate models (CPRCMs) offer a valuable tool to better understand these processes. This study evaluates integrated water vapor transport (IVT) and precipitation in the Amazon Basin using a CPRCM simulation during austral summer (DJF) and winter (JJA). Simulations at 4.5 km resolution cover most of South America and are validated using ERA5 reanalysis. The CPRCM-ERA experiment (1998–2007) was driven by ERA-Interim data and downscaled to 25 km with an RCM. During DJF, precipitation was overestimated in the central Amazon (+ 1.0 to + 2.0 mm/day) and underestimated in the northeastern and western Amazon (− 2.5 mm/day). The CPRCM-ERA simulation showed a weaker low-level jet (LLJ) and trade winds. IVT analysis indicated a negative bias in moisture transport over the LLJ region, more pronounced in CPRCM-ERA. This model underestimated moisture inflow by 6.1% and outflow by ~ 20%, while the RCM showed smaller biases (inflow + 0.8%, outflow + 7%). In JJA, biases differed: CPRCM-ERA underestimated moisture inflow by 4.7% and outflow by 4.6%, while RCM overestimated both (inflow + 8.2%, outflow + 7.5%). This study provides a detailed comparison between convection-permitting and parameterized regional climate simulations, highlighting how dynamic and thermodynamic mechanisms shape moisture transport biases across the dry and the wet seasons. By evaluating the processes involved, the analysis clarifies the strengths and limitations of using CPRCMs over the Amazon Basin and offers guidance for improving future high-resolution modeling of the South American hydrological cycle.